Pro mundo-pro domo : the writings of Alban Berg - Berg, Alban, 1885-1935 (Oxford University Press, 2014)
Pro Mundo - Pro Domo: The Writings of Alban Berg contains new English translations of the complete writings of the Viennese composer Alban Berg (1885-1935) and extensive commentaries tracing the history of each essay and its connection to musical culture of the early twentieth century. Berg is now recognized as a classic composer of the modern period, best known for his operas Wozzeck and Lulu. Berg, Anton Webern, and their teacher Arnold Schoenberg constitute the ""Second Viennese School"" which played a major role in the transformation of serious music as it entered the modern period. Berg w